Menopause as a Stage of Life and A Guide to A Healthy Menopause Transition - T. Nagamani; P. Venkata Suresh; P. Bhargavi; K. Sesha Kumar; P.V. Savitha; K .R. Rajani (International Journal of Midwifery Nursing And Practices, 2023)
Menopause is a normal physiological stage of life of a woman that occurs between 45 and 55 years of age group. When a woman enters menopause, her ability to conceive and her ovarian activity permanently cease. The menopausal transition is a crucial factor in many symptoms that are prevalent in middle age and may be linked to chronic illnesses and aging-related disorders. Appropriate identification and treatment of signs and symptoms of menopause help to prevent complications such as obesity, osteoporosis, heart disease, etc. A healthcare provider plays a major role in creating awareness and providing supportive services to women. Through a lifestyle approach, we can improve the quality of life of women during the menopausal transition.
Keywords: Menopause; PMS; dyspareunia; obesity; osteoporosis